"I'll just deal with this on my own": a qualitative exploration of experiences with self-managed abortion in the United States - Sarah Raifman; Lauren Ralph; M. Antonia Biggs; Daniel Grossman (BMC, 2021)
Plain language summary Some people in the United States (US) attempt to end a pregnancy on their own without medical supervision. What we know about this experience comes from studies focused on people who go to clinics. In this study, we conducted 14 interviews with self-identified women ages 18-49 who recently reported attempting to end a pregnancy on their own and who were recruited outside of the clinic setting. We asked participants about their fertility histories, experiences seeking reproductive health care, and experiences ending a pregnancy without medical assistance. Those who took a pregnancy test and then chose to end the pregnancy on their own did so because it was convenient, accessible, and private. Those who did not test for pregnancy felt empowered by the ability to try something on their own before seeking facility-based care. All participants prioritized methods that were safe and available, though not always effective. After they attempted to end the pregnancy on their own, five participants accessed abortion care in facilities, one decided to continue the pregnancy, and eight were no longer pregnant. Our findings show that, in addition to people who end a pregnancy on their own as a last resort (after facing barriers to facility-based care) or as a first resort (because of preferences for homeopathic methods), a third group values having an interim step to try after suspecting pregnancy and before accessing facility-based care. These people would particularly benefit from a medication abortion product available over the counter, online, or in the form of a missed-period pill.